Positioning the Portrayal of White Protagonists in O.A Bushnell’s the Return of Lono and Ka’a’awa - Kristiawan Indriyanto; Ida Rochani Adi; Muh. Arif Rokhman (Journal of Language and Literature, 2021)
This paper explores the role of literature in the post-truth age through reading on O.A Bushnell’s the Return of Lono and Ka’a’awa. A Hawai’ian novelist, Bushnell contextualizes the earliest interactions between the native Hawai’ian (Kanaka Maoli) and the white settlers which began with the arrival of Captain Cook’s expedition in 1778. Through his fictions, Bushnell underlines positive portrayal of the white characters to provide a counter-discourse to the generally accepted history of Hawai’ian colonialism. Through first person point of view, white characters become the central figure in both of Bushnell’s fictions. Through reading on O.A Bushnell’s narration, this paper aims to elaborate how the Hawai’ian natives also become a willing partner in western colonialism which highlights their colonial complicity. The concept of colonial complicity is employed to highlight the participation of the natives in promoting Western way of thinking. The analysis argues that although Bushnell contextualizes the complicity of the Hawai’ians in promoting Western discourse, resistance also occurs through creation of a hybrid culture.  This paper concludes that in the post truth era, literature should always strive to uncover the truth based on subjective interpretation instead of abiding of a universal truth.